Developing Exon‐Primed Intron‐Crossing (EPIC) markers for population genetic studies in three Aedes disease vectors. (7th August 2014) - White, Vanessa Linley; Endersby, Nancy Margaret; Chan, Janice; Hoffmann, Ary Anthony; Weeks, Andrew Raymond
Abstract Aedes aegypti, Aedes notoscriptus, and Aedes albopictus are important vectors of many arboviruses implicated in human disease such as dengue fever. Genetic markers applied across vector species can provide important information on population structure, gene flow, insecticide resistance, and taxonomy, however, robust microsatellite markers have proven difficult to develop in these species and mosquitoes generally. Here we consider the utility and transferability of 15 Ribosome protein (Rp) Exon‐Primed Intron‐Crossing (EPIC) markers for population genetic studies in these 3 Aedes species. Rp EPIC markers designed for Ae. aegypti also successfully amplified populations of the sister species, Ae. albopictus, as well as the distantly related species, Ae. notoscriptus. High SNP and good indel diversity in sequenced alleles plus support for amplification of the same regions across populations and species were additional benefits of these markers. These findings point to the general value of EPIC markers in mosquito population studies.